RETURN SAHAM MELALUI KEBIJAKAN DIVIDEN SEBAGAI VARIABEL MODERASI: MANAJEMEN LABA, UKURAN PERUSAHAAN DAN PROFITABILITAS: STOCK RETURN THROUGH DIVIDEND POLICY AS A MODERATING VARIABLE: EARNINGS MANAGEMENT, COMPANY SIZE AND PROFITABILITY - Saputra, Deni (AKUNTANSI DEWANTARA, 2023)
This study aims to determine the effect of earnings management, company size and profitability on stock returns with dividend policy as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange in 2016 - 2020. With a total sample of 61 manufacturing companies. The sampling technique used is the Purposive Sampling method where the number obtained in this study is 61 companies and as a sample with observations as many as 305 observations. The analytical method used is panel data regression.The results of this study conclude that: (A) Earnings Management has no significant effect on stock returns in manufacturing companies listed on the Indonesia Stock Exchange. (B) Partial company size has a significant effect on stock returns. (C) Partial profitability has no significant effect on Stock Return. (D) Earnings Management, Firm Size and Profitability have a joint effect on Stock Return. (E) Partial Earnings Management has no significant effect on Stock Return with dividend policy as a moderating variable. (F) Firm size has a significant effect on Stock Return with dividend policy as a moderating variable. (G) Profitability has a significant effect on Stock Return with dividend policy as a moderating variable.